Internet Banking Service Quality and Customer Retention in Deposit Money Banks in Rivers State- Nigeria - Ezechirinum, AAmadi; Victor C., Anucha; Osagie Leslie, Uwabor (British Journal of Marketing Studies, 2020)
This study investigates the relationship between Internet Banking Service Quality and Customer Retention in Deposit Money Banks in Rivers State. The objectives of the study were to investigate the influence of internet service efficiency and website design on Customer Retention. The study adopted the quasi-experimental research design which employed the cross sectional survey design. The choice of this survey approach is because it will scientifically look at the situation on ground and will empirically analyze it to get result that can be attributable to the accessible population. Based on the research questions, a research questionnaire was designed and one hundred and ninety (190) copies were distributed to the customers of the banks who constituted the populationof study, the researcher purposively administered ten (10) copies each to customers of the nineteen (19) deposit money banks in Rivers State. A total of one hundred & sixty-nine (169) copies of the distributed questionnaire were retrieved. These copies were analyzed and the hypotheses were tested using the Kendal’s Correlation Coefficient with the aid of SPSS Version 23.0. The result revealed that; there is a significant relationship between internet banking service efficiency and referral, internet banking service efficiency and resistance to competitive pressure, Internet banking website design and referral, Internet banking website design and resistance to competitive pressure. The result also revealed that customer technology adoption positively influences the relationship between internet banking service quality and customer retention in deposit money banks in Rivers State. The study concluded that consumer orientation should be applied whenever; banks are adopting new techniques that will service the need of their customers for better satisfaction. The study recommends that Banks should invest more on technologies that will ensure efficiency in serving customer and overall satisfactions of the customers. Customer satisfaction should be kept in mind as banks upgrade existing systems or while buying new systems altogether.